The architecture of Istana Jahar: apprehend the parameters of historical changes - Nik Din, Nik Abdul Aziz; Rashid, Md. Mizanur; Salleh, Nurul Hamiruddin (2014)
This study aims to explore the unrevealed history of Istana Jahar, Kota Bharu, Malaysia, which has gone through numerous changes in terms of functions due to several reasons that give the impacts to its architecture. However, the discontinued historical narrative failed to provide reasons of these changes. This research will set and argue that certain parameters might be responsible for these changes and if identified, these parameters will provide a solid platform to understand the building and its architecture through ages. Hence, to capture the historical changes and its influences from the minimal sources, it is imperative to distinguish the nature of these parameters. This research will carry out the task to collect information for setting up the parameters which has significant to the changes of the in the architecture of Istana Jahar. The scope of this paper will be limited to focus on political and social parameters which have significant impacts in architectural changes of Istana Jahar. Istana Jahar is a royal testimonial that has its own prides and its architecture indeed played the significant roles to its socio-political changes in the society. By citing the case study of Istana Jahar, this research will argue on the current condition of Istana Jahar in relation to its original condition base on the political parameters to the architecture. This research will provide a research framework of the Istana Jahar and cultivate the eagerness to explore other possibilities in unveiling the architectural history in different ways. By combining layers of information, this research would provide a further platform to explore any others possibilities for the architectural historian to capture the information especially heritage buildings and help to foster a better architectural identity of Malaysia. Thus, this paper discusses for the need of apprehending the possible changes parameters of a historical building along with the proofs to capture a comprehensive data of historical building.